Factor Structure and Psychometric Properties of the Comprehensive Inventory of Mindfulness Experiences among University Students - Elmira Golparvari; Mehrdad Sabet (Shahid Beheshti University of Medical Sciences, 2019)
Background and Objective: Mindfulness is a multidimensional construct and its various dimensions can play an important role in reducing and improving the symptoms and physical and emotional symptoms of people with various disorders which makes the evaluation of mind-awareness necessary. The purpose of the present study was to investigate the factor structure and psychometric properties of a comprehensive inventory of mindfulness experiences among university students. Materials and Methods: The method of this study was correlation and factor analysis. The statistical population of this study included all students of Islamic Azad University of Roudehen Branch who were studying in the first half of the academic year 2018-19, among whom 473 students were selected by convenience sampling method. To obtain data, the comprehensive inventory of mindfulness experiences (CHIME-A) and mindfulness scale (MAAS) were used. Data were analyzed by using correlation coefficient and exploratory factor analysis methods via SPSS software version 22. Results: The mean (SD) age of the participants was 25.1 (6.2) among male students and 23.8 (5.4) among female students. CHIME-A consisted of three components. The mean (SD) score of the component of perception with active insight and decentralization was 52.3 (9.5); component of knowledge of internal and external experiences 48.7 (6.5); action with knowledge, acceptance and orientation without judgment 26.4 (5.9) and Cronbach's alpha coefficient was 0.85, 0.72 and 0.61, respectively. The mean (SD) total score of the questionnaire was 127.5 (14.8) and its Cronbach's alpha coefficient was 0.90. The three components of CHIME-A and their total score were positively correlated with the scores of MAAS (P <0.01). Conclusion: The study showed that the comprehensive inventory of mindfulness experiences among students has an appropriate internal consistency and validity. DOI: http://doi.org/10.22037/ch.v6i4.23349